Substance use, harm reduction attitudes and behaviors among attendees of nature rave parties in Israel - Hagit Bonny-Noach; Barak Shapira; Pinchas Baumol; Nir Tadmor; Paola Rosca; Stacy Shoshan; Yossi Harel-Fisch; Ariel Caduri (BMC, 2023)
Abstract Background Few studies have analyzed harm reduction behaviors and attitudes among rave party attendees. Since the late 1980s, there has been a large Israeli rave scene, also known as 'Nature Parties'. However, only a few studies have been conducted among nature party attendees and almost all of them are from a qualitative perspective. This study's aim was to fill the gap and conduct quantitative research to investigate the patterns of substance use, harm reduction attitudes and behaviors among Israeli nature rave party attendees. Methods A cross-sectional online survey recruited 1,206 people who reported having attended nature rave parties. All of the participants were aged 18-60 years (M = 29.9; SD = 7.4), and 770 (64%) were male. Results The most common illicit substances used at Israeli nature rave parties in the past year were cannabis (62.2%), followed by LSD (41.4%), MDMA (31.7%), mushrooms/psilocybin (23.9%), ketamine (19.6%) and cocaine (17.2%). A significant but weak association was found between harm reduction behaviors and attitudes toward harm reduction interventions (r = .26, p < .001) and attitudes toward drug testing kits (r = .33, p < .001). It seems that although we found higher positive harm reduction attitudes, it is harder to implement harm reduction behaviors. Logistic regressions demonstrated stronger associations with high harm reduction behaviors and higher levels of positive attitudes toward drug testing kits (OR = 4.53; CI 2.97-6.90; p < .001), higher levels of positive attitudes toward harm reduction interventions (OR = 4.06; CI 2.62-6.29; p < .001), marital status of widower/divorced (OR = 2.22; CI 1.49-3.32; p < .001), using MDMA (OR = 1.63; CI 1.19-2.23; p <  = .01) and using LSD (OR = 1.41; CI 1.03-1.94; p <  = .05). Conclusions Formal harm reduction policies and interventions are needed for Israeli nature rave parties in addition to prevention and information programs, which are also very rare. Future studies should examine the subjects of harm reduction attitudes and behaviors among the public, policy makers and professionals.